Cancer Risk Among Children Undergoing Renal Replacement Therapy: Results From the Israel National Renal Replacement Therapy Registry, 1990-2012. Issue 8 (November 2018) - Nuss, Naama; Libruder, Carmit; Dichtiar, Rita; Weinstein, Talia; Keinan-Boker, Lital; Shohat, Tamy; Golan, Eliezer
Abstract : Background: Patients with end-stage renal disease who undergo chronic renal replacement therapy (RRT) have a higher incidence of cancer. A limited number of studies addressed the risk for cancer in children exposed to RRT. The purpose of the present study was to examine whether children undergoing RRT in Israel are at increased risk for all-site and specific cancers. Subjects and Methods: The study population comprised 674 children 0 to 19 years of age who were registered between January 1990 and December 2012 in the Israel National Renal Replacement Therapy Registry. The Registry database was linked with the Israel National Cancer Registry to trace cancer incidence. Variables associated with malignancy were estimated by univariate analysis. Standardized incidence ratios for cancer were calculated using the general Israel population 0 to 15 years of age, for the corresponding years 1990-2012, as a reference. Results: Seventeen children developed cancer during the follow-up period. Younger age at RRT initiation was the only variable associated with malignancy in the univariate analysis (hazard ratio, 0.91; 95% confidence interval, 0.84-0.99; P =0.03). Cancer incidence was 6.7-fold higher among children undergoing RRT than the general population. Conclusions: Children treated by chronic RRT have a higher incidence of cancer than their peers, and therefore should be followed closely.